Design and Development of Patient Monitoring System - Azizulkarim, Azra Hazwanie; Abdul Jamil, Muhammad Mahadi; Ambar, Radzi (IOP conference series. Materials Science and Engineering, 2017)
Patient monitoring system allows continuous monitoring of patient vital signs, support decision making among medical personnel and help enhance patient care. This system can consist of devices that measure, display and record human's vital signs, including body temperature, heart rate, blood pressure and other health-related criteria. This paper proposes a system to monitor the patient's conditions by monitoring the body temperature and pulse rate. The system consists of a pulse rate monitoring software and a wearable device that can measure a subject's temperature and pulse rate only by using a fingertip. The device is able to record the measurement data and interface to PC via Arduino microcontroller. The recorded data can be viewed as a historical file or can be archived for further analysis. This work also describes the preliminary experimental results of the selected sensors to show the usefulness of the sensors for the proposed patient monitoring system.